2013
DOI: 10.1088/0957-4484/24/47/475202
|View full text |Cite
|
Sign up to set email alerts
|

Flexible graphene–PZT ferroelectric nonvolatile memory

Abstract: We report the fabrication of a flexible graphene-based nonvolatile memory device using Pb(Zr0.35,Ti0.65)O3 (PZT) as the ferroelectric material. The graphene and PZT ferroelectric layers were deposited using chemical vapor deposition and sol–gel methods, respectively. Such PZT films show a high remnant polarization (Pr) of 30 μC cm−2 and a coercive voltage (Vc) of 3.5 V under a voltage loop over ±11 V. The graphene–PZT ferroelectric nonvolatile memory on a plastic substrate displayed an on/off current ratio of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 38 publications
2
61
0
Order By: Relevance
“…Hussain and co‐workers reported a high performance and a low‐cost batch fabrication process for PZT‐silicon–based flexible ferroelectric capacitors that can be used for nonvolatile memory applications . Several other similar studies, including flexible graphene‐PZT–based ferroelectric systems, also reveal the importance of ferroelectric materials for memory applications …”
mentioning
confidence: 90%
“…Hussain and co‐workers reported a high performance and a low‐cost batch fabrication process for PZT‐silicon–based flexible ferroelectric capacitors that can be used for nonvolatile memory applications . Several other similar studies, including flexible graphene‐PZT–based ferroelectric systems, also reveal the importance of ferroelectric materials for memory applications …”
mentioning
confidence: 90%
“…Table 1 summarizes the basic properties of the flexible system in this study and several reported flexible ferroelectric memory elements. [27,28,[37][38][39][40] Note that the bendable PZT film was directly grown on mica via a simple and cost-effective CSD method using the spin coating technique in this work, and the ferroelectric (P r ≈ 30 μC cm −2 ) and dielectric response Adv. Electron.…”
Section: Resultsmentioning
confidence: 99%
“…However, PZT-based flexible FeRAM was not achievable on organic platforms because of PZT's high crystallization temperature (>600 °C), well above the melting temperature of most polymeric organic substrates. Hence, PZT FeRAMs have been demonstrated only on flexible silicon and platinum foil [229,230] or built on silicon and then transferred to polymeric flexible substrates [84,231]. Nevertheless, the highest level of mechanical durability (20,000 bending cycles) has been reported for hybrid FeRAMs with inorganic devices transferred to a polymeric substrate [232,233].…”
Section: Flexible Ferammentioning
confidence: 99%
“…As of today variety of materials have been used to build NVM devices. For example, NMVs based on; (i) embedded 0-dimensional gold nanoparticles (NPs) [73][74][75][76][77], black phosphorous quantum dots (QDs) [78], and silicon QDs [79]; (ii) 1-dimensional zinc oxide (ZnO) nanowires [48], silicon (Si) nanowires [80], and carbon nanotubes (CNTs) [81][82][83]; and (iii) 2-dimensional graphene [49,84,85], graphene oxide [46,[86][87][88][89][90][91], molybdenum disulfide (MoS2) [50,92], zinc oxide (ZnO) [48], and hydrated tungsten tri-oxide (WO3.H2O) nano-sheet [29] have already been reported.…”
Section: Introductionmentioning
confidence: 99%